2021
DOI: 10.1111/mec.16253
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive divergence in bill morphology and other thermoregulatory traits is facilitated by restricted gene flow in song sparrows on the California Channel Islands

Abstract: Disentangling the effects of neutral and adaptive processes in maintaining phenotypic variation across environmental gradients is challenging in natural populations.Song sparrows (Melospiza melodia) on the California Channel Islands occupy a pronounced east-west climate gradient within a small spatial scale, providing a unique opportunity to examine the interaction of genetic isolation (reduced gene flow) and the environment (selection) in driving variation. We used reduced representation genomic libraries to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 129 publications
(209 reference statements)
1
9
1
Order By: Relevance
“…Another possible explanation for changes in bill dimensions at the locality level is thermoregulation, as bill surface has been shown to increase in hot, dry environments to facilitate heat dissipation (Tattersall et al, 2017). We found no evidence for this hypothesis in La Palma chaffinches, and found no correlation between bill surface and temperature, in contrast with other studies where birds found in colder environments had smaller beaks (Gamboa et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…Another possible explanation for changes in bill dimensions at the locality level is thermoregulation, as bill surface has been shown to increase in hot, dry environments to facilitate heat dissipation (Tattersall et al, 2017). We found no evidence for this hypothesis in La Palma chaffinches, and found no correlation between bill surface and temperature, in contrast with other studies where birds found in colder environments had smaller beaks (Gamboa et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, local adaptation in the face of gene flow appears common even in taxa with a high dispersal potential (Richardson et al, 2014). For example, other avian systems have been shown to exhibit evolutionary responses in multiple morphological (Bertrand et al, 2016; Cornuault et al, 2015) and physiological traits (Gamboa et al, 2022; Mikles et al, 2020) within the potential dispersal radius of the study species. Understanding such fine‐scale adaptation requires multiple lines of evidence, including trait variation across environmental gradients and within the dispersal neighbourhood of the species in question, evidence for divergent selection across the environmental gradient, and observed phenotypic variation that must be at least partially genetically based.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found genetic differentiation across fine spatial scales in several avian species related to physiological and reproductive adaptive divergence between habitats (e.g., Charmantier et al, 2016; García‐Navas et al, 2014; Mikles et al, 2020; Perrier et al, 2020; Senar et al, 2006). We hypothesize that the signature of divergent selection at these loci could be attributed to environmental differences between habitats driven by the climate gradient induced by the California Current: Santa Cruz Island is characterized by more arid conditions in the east and a cooler climate in the west (Fischer et al, 2009; Gamboa et al, 2022; Morrison et al, 2011). Given that birds exhibit strong physiological responses to extreme heat (Mckechnie & Wolf, 2009), the island's pronounced east–west climate gradient could lead to divergence in physiological or behavioural traits in the island scrub‐jay.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, as with genetic differentiation, the extent of phenotypic structuring varied across species, with bill and body size being significantly different between deserts in a few taxa, but somewhat surprisingly, environmental variation did not usually explain morphological differences. For example, adaptations in bill morphology are frequently observed, such as in Song Sparrows on the Channel Islands that have higher bill surface area in hotter climates ( Gamboa et al 2021 ). The lack of a tight correlation between environment and phenotype in our study were likely reflective of the shallowness of the evolutionary divergences and the subtlety of the environmental gradient across deserts.…”
Section: Discussionmentioning
confidence: 99%